Effects of the COVID-19 pandemic on academic preparation and performance: a complex picture of equity - Burkholder, Eric W.; Salehi, Shima (Frontiers in Education, 2023)
Introduction Many experts have predicted a drop in students’ academic performance due to an extended period of remote instruction and other harmful effects of the pandemic. Methods As university instructors and education researchers, we sought to investigate the effects of the pandemic on students’ preparation for college-level coursework and their performance in early college using mixed effects regression models. Data were collected from STEM students at a public research university in the southeastern United States. Results We found that demographic gaps in high school preparation (as measured by ACT scores) between men and women, as well as underrepresented minority and majority students, remained relatively consistent after the start of the pandemic. These gaps were approximately 1 point (out of 36) and 3 points, respectively. However, the gap between first generation and continuing generation students increased from prior to 2020, to after 2020, going from approximately 1 point to 2 points. This gap in preparation was not accompanied by a corresponding shift in the demographics of the student population and there was no corresponding increase in the demographic gaps in students’ first term grades. Discussion The data seem to suggest that first-generation students in STEM suffered more from the changes to secondary instruction during the pandemic, but that college instructors were able to mitigate some of these effects on first-semester grades. However, these effects were only mitigated to the extent that they preserved the status quo of pre-pandemic inequities in undergraduate STEM education.